CHALLENGES AND BUSINESS OPPORTUNITIES FOR THE DEVELOPMENT OF MANCHU EMBROIDERY AS A TOURISM SOUVENIR PRODUCT IN JILIN CITY - Sun zengyu; Hanisa Hassan, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
There is a unique type of embroidery in Jilin called Manchu embroidery. The Manchu is an ethno-linguistic group in northeast China. The town of Ula Manchu is located in Jilin City and has a history of more than 600 years. It is one of the important birthplaces of the Manchu people. It still retains Manchu cuisine from the Qing Dynasty, which has become an important tourist resource. Meanwhile, Jilin City also has a famous international ski resort. Every year, tourists from all over the world look forward to the food and specialties of Ula Street Manchu Town. Current Manchu embroidery souvenir products are misleading in terms of cultural expression product development. Given the potential of Manchu embroidery souvenirs to improve the local tourism economy and the recognition of this ethnic culture, this study aims to identify the unsuitable pattern categories in its Manchu embroidery culture for development as tourism products and to assess the business opportunities and challenging environment for developing Manchu embroidery. This study adopts a qualitative method to identify the potential and obstacles of developing Manchu embroidery into a tourism product. At the same time, it provides more thinking about the material culture protection methods of the Ula Manchu. This study adds to the literature on the Ula Manchu and can be used as a solution to the problem of indigenous tourism. industry-related issues that can be addressed with the support of policy interventions.